Stepping Toward Business Excellence: Building an Integrated and Efficient Enterprise Architecture System - Andi Naila Quin Azisah Alisyahbana; Fajriani Azis; Muhammad Faris Fardhani; Muhammad Ikhwan Rauf; Andika Isma (Global Research and Collaboration, 2023)
In today's digital era, businesses face increasingly complex challenges. To achieve business excellence, organizations need to build integrated and efficient systems. Enterprise architecture (EA) is a comprehensive approach to designing and managing information technology and business structures in organizations. This journal aims to investigate the importance of building an integrated and efficient EA in achieving business excellence. We use a research methodology approach to analyze case studies and results related to EA implementation in several organizations. Our findings show that an integrated and efficient EA can provide benefits such as improved operational efficiency, cost savings, increased flexibility, and better decision-making. In this journal, we describe the methods used in building EAs, the results of EA implementation in organizations, and a discussion of the implications and resulting benefits. We conclude that building an integrated and efficient EA is an important step for organizations that want to achieve business excellence. An integrated and efficient EA in achieving business excellence. An integrated EA involves a comprehensive planning and design process, integration of systems and applications, effective data and information management, and necessary organizational changes. An integrated and efficient EA implementation can provide a number of benefits to an organization, including improved operational efficiency, reduced costs, increased visibility and accessibility of information, and better decision-making. However, the challenges and complexities associated with EA implementation need to be addressed through a holistic approach, stakeholder engagement, effective communication, and proactive change management.